Penggunaan Cryptography dalam Keamanan Pesan Digital - Setiawan, Adi Bima (Lembaga Publikasi Ilmiah Nusantara, 2025)
The rapid development of information technology has facilitated digital communication processes, but on the other hand, it increases the risk of data leakage and misuse. One solution widely used to secure digital messages is the application of cryptography technology. Cryptography plays a crucial role in maintaining the confidentiality, integrity, and authenticity of information by converting messages into a format that cannot be read without the appropriate key. This study aims to analyze the use of cryptographic methods in maintaining the security of digital messages, with a focus on symmetric and asymmetric encryption techniques. The research method used is a literature review from various scientific sources and simulation implementation to test the effectiveness of cryptographic algorithms against cyberattacks. The results show that symmetric cryptography has a higher processing speed, while asymmetric cryptography excels in key management and authentication. The combination of the two through a hybrid encryption mechanism has been proven to increase the level of security without sacrificing performance. The proper application of cryptography not only protects messages from unauthorized access but also supports trust in digital communication. This study recommends the integration of modern cryptographic algorithms such as AES and RSA in digital messaging applications to achieve optimal protection.